Bioavailability of Amino Acids of Soybean Meal in Broilers Subjected to Heat Stress - Farjam, Abdoreza Soleimani (2006)
The effect of high ambient temperature (35 vs 21°C) and acclimation during 5 and 6 week of age on the bioavailability of protein and amino acids was investigated in broilers. Two experiments were conducted to achieve the above objectives. In both experiments, equal numbers of chickens (90 birds: 45 Male, 45 Female) were assigned to three groups namely 2 weeks heat stress (heat acclimated), I week heat stress (non-heat acclimated) and no-heat stress. During the 28-35 days, the 2 weeks heat stress group was challenged to heat stress for 180-min every day. During the 35-43 days, the 1 week heat stress group was challenged to heat stress as well. The no-heat stress group was kept in standard temperature (21 °C) as control. Basal diet which contained soybean meal as a sole source of protein was fed to all birds during day 39-41 as adaptation period. Following this, the birds undergone 24 h fasting. Assay diet was then fed to all birds for one hour before starting the heat challenge. For Experiment I, Assay diet was the same with basal diet without methionine suplimentation and for Experiment 2, it was a nitrogen free diet. Feed conversion ratio (FCR) and deep body temperature (Tb) were measured and distal ileum contents were collected from birds killed by intravenous injection of sodium pentobarbitone through wing vain, immediately after heat challenge. The assay diet for second experiment was a nitrogen-free diet to investigate the endogenous protein and amino acid (AA) output. FCR increased by heat stress (P < 0.05). Heat acclimation resulted in 20% improvement in FCR in 2wk heat stressed birds as compare with non-heat acclimated birds (1 wk heat stress) at 3 5-43 days. Tb of both heat stressed groups increased throughout the heat stress period. 2wk heat stressed birds had significantly lower Tb than l wk heat stressed birds in day 35 and 37 (P < 0.05), but there was no difference at day 39 (P > 0.05). Crude protein and total amino acids apparent and true digestibility was significantly depressed by heat stress (P < 0.05) and this reduction failed to be improved by heat acclimation. Moreover, the reduction was found in all amino acid except for glutamic acid, aspartic acid, methionine, tryptophan, serine, alanine and proline. Acclimation and sex had no effect on total AA availability. Also there was no interaction between sex and heat challenge duration (P > 0.05). The mean AA availability of soybean meal observed in the present study was 82% in no-heat stress group and 78% in heat stressed birds. The relatively low values of AA availability in this study may be attributed to the soybean meal quality which was suspected to be underprocessed. One of the striking findings of this study was the low availability value for tyrosine under heat stress condition (11.9% less than no heat stress) which was the lowest among other AA. Analysis of endogenous excretion from the second experiment revealed that glutamic acid, aspartic acid, serine, threonine, leucine and arginine were the predominant endogenous amino acids present in ileal output. In addition, the lowest ileal endogenous AA losses were tryptophan, methionine and cystine.